CHARACTERISTICS OF MENTAL DISORDERS AMONG PATIENTS RECEIVING METHADONE TREATMENT AT THE HUNG YEN CENTER FOR DISEASE CONTROL, FACILITY 2 AND ASSOCIATED FACTORS (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the characteristics of mental disorders among patients undergoing Methadone treatment at the Hung Yen Center for Disease Control, facility 2, in 2024, and to identify associated factors.Research methods: An analytical cross-sectional study was conducted on 228 Methadone patients from March to August 2024. Data collection tools included a structured questionnaire, medical record review forms, and the DASS-21 scale for mental health assessment. Data were processed using SPSS 20.0, employing Chi-square tests and OR to determine associations with statistical significance set at p < 0.05.Results: The study participants were predominantly male (98.7%), with an average age of 45.0 ± 6.9 years. The prevalence of risk for depression, anxiety, and stress was 15.8%, 30.7%, and 12.7%, respectively. Psychological disorders were most concentrated in the 40-49 age group, those with a secondary school education level, and those with a treatment duration ≥ 2 years. The study identified a statistically significant association between marital status and both depression and stress. Specifically, patients who were single, separated, or divorced had a 2.8 times higher risk of depression (95% CI: 1.3-5.9) and a 3.8 times higher risk of stress (95% CI: 1.6-8.5) compared to married individuals. No significant association was found between anxiety and demographic factors or the surveyed treatment duration.Conclusion: The prevalence of mental health disorders among Methadone patients at the Hung Yen Center for Disease Control, facility 2, is significant, with anxiety being the most prevalent issue. Marital status is a crucial factor influencing the risk of depression and stress. These findings suggest the need for enhanced periodic mental health screening and the implementation of psychological support therapies, particularly for patients lacking family support.
Keywords: Depression, anxiety, stress, Methadone.